Analisis Konten Edukasi Kesehatan Mental Di Instagram (Analisis Isi Kualitatif Pada Akun Instagram @Studiodjiwa) - Triuli Tresia; Yanto Yanto; Bayu Risdiyanto (Universitas Dehasen Bengkulu, 2024)
Research purposes will that publish mental health educational content, one of which is the @Studiodjiwa account, is the background for this research. The aim of this research is to analyze the content of mental health educational content on Instagram on the @Studiodjiwa account. Mental health has become an important issue in the modern era, with Instagram a popular social media platform for education. This research uses the Holsti content analysis method, a research technique for making objective inferences and systematic identification of message characteristics answering the questions What, To Whom, How. The research data was obtained from 6 pieces of content published in the November-December 2023 edition which were then determined by describing the recording unit and context unit. This analysis also focuses on the characteristics of educational messages based on mental health characteristics, namely Positive Mental Health, Mental Health Problems, Mental Disorders. The research results show that @Studiodjiwa presents a variety of mental health educational content, including the definition of empathy, personality depending on other people, hobbies, films, emotional intelligence and the causes and strategies for handling various mental health problems. Content is packaged in the form of infographics, images, videos and text that are informative and educational. The selected content dominates with Positive Mental Health characteristics, the messages are aimed at followers of the @Studiodjiwa account or those who see the posts, and the message techniques used are more persuasive.